A huge oceanic-type UHP metamorphic belt in southwestern Tianshan, China: Peak metamorphic age and P-T path - Zhang, L.; Du, J.; Lü, Z.; Yang, X.; Gou, Long-Long; Xia, B.; Chen, Z.; Wei, C.; Song, S. (2013)
Recent progress in the study of the UHP metamorphic belt in southwestern Tianshan, China, is summarized in this paper. This about 80-km-long and over 10-km-wide UHP belt has been recognized by the discovery of coesite, coesite pseudomorphs and other UHP minerals. It is the largest oceanic-type UHP metamorphic belt reported so far. It has formed due to northward subduction of the Tianshan Paleo-Ocean. U-Pb dating of metamorphic rims of zircons from a coesite-bearing garnet-phengite schist yields a peak UHP metamorphic ages of 320±3.7 Ma. Combined with ages of 233-226 Ma obtained from rims of zircons from retrograded eclogites, a long retrograde metamorphic evolution (>70 Ma) has been revealed. According to phase equilibria modeling, the P-T paths of both coesite-bearing eclogites and garnet-phengite schists are characterized by thermal relaxation, i.e., the metamorphic temperature peak lags behind the pressure peak, indicating that the UHP rocks experienced slow and long heating and decompression during exhumation in the subduction channel. On the basis of the field observation that a small amount of eclogite lenses is wrapped in large volumes of metapelites, and the similar P-T paths of both rock types, we propose that the exhumation of the UHP eclogites from southwestern Tianshan, China, may have resulted from the exhumation of large volumes of low-density metapelites, which carried the denser eclogites to the Earth's surface. © 2013 The Author(s).